Resorcinol as Protective Agent in Thermochemical Modification of Lysozyme - Grzegorz Lesnierowski; Renata Cegielska-Radziejewska; Jerzy Stangierski; Robert Borowiak (Food Technology and Biotechnology, 2013)
Thermochemical modification of lysozyme enables it to retain its oligomers, showing a wide spectrum of increased antibacterial activities. It also results in significant loss of hydrolytic activity of the enzyme. The objective of this study is to analyse the protective effect of resorcinol on the hydrolytic activity of modified lysozyme using a high temperature method and the oligomerization degree in the obtained preparations. Resorcinol significantly affects the enzyme’s hydrolytic activity. Samples containing resorcinol, without oxidizing agent, modified at 90 °C retained 75 % enzymatic activity of unmodified monomer, obtaining the final value of about 16 000 U/mg. The amount of lysozyme oligomers increased slightly in the samples produced under such conditions.